The reform of parliament: an alternative proposal - Sardón, Jose Luis (1991)
This article argues in favour of a re-definition of Parliament's role in Peru. In the contemporary world, public affairs change too fast or are too complexes to name Parliament the direct responsible of ordering them through legislation. Thus, the main duty of this institution should be not to legislate but to elect and control the Executive Branch of government.